FUNDING-RELATED ADMINISTRATIVE IMPEDIMENTS TO THE EFFECTIVE IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION PROGRAMME IN UNIVERSITIES INSOUTH-EAST NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The laudable objectives of entrepreneurship education have not been achieved because of thechunk of graduates unemployed, seemingly due to lack of requisite skills for employment inmodern offices. This problem prompted this study to investigate funding-related administrativeimpediments to the effective implementation of entrepreneurship education programme inuniversities insouth-east Nigeria. One research questions guided the study while two nullhypotheses were formulated. The study adopted a descriptive survey research design. The entirepopulation of 79 administrative staff of entrepreneurship development centres in universities inSouth East, Nigeria was used for data collection. Questionnaire was used to collect data. Thequestionnaire was validated by three experts, and its internal consistency yielded a co-efficientvalue of 0.79 using Cronbach Alpha Method was obtained. Mean and standard deviation wasused to answer the research questions while t-Test was used to test the null hypotheses at 0.05level of significance. Findings revealed that administrative staff of entrepreneurshipdevelopment centres agreed on funding-related administrative impediments to the effectiveimplementation of the entrepreneurship education programme in universities in South EastNigeria.
Keywords: Funding, administration, impediments, entrepreneurship education